Use of high-performance polymeric materials in customized low-cost robotic grippers for biomechatronic applications: experimental and analytical research - Păcurar, Răzvan Ioan; Sanfilippo, Filippo; Økter, Martin Bjaadal; Băilă, Diana-Irinel; Zaharia, Cătălin; Nicoară, Adrian Ionuţ; Radu, Ionuț Cristian; Savu, Tom; Górski, Filip; Kuczko, Wiesław; Wichniarek, Radosław; Comşa, Dan Sorin; et al. (Frontiers in Materials, 2024)
Advancements in materials science and 3D printing technologies have opened up new avenues for developing low-cost robotic grippers with high-performance capabilities, making them suitable for various biomechatronic applications. In this research, it has been explored the utilization of high-performance polymer materials, such as Polyetherketoneketone (PEKK), Polyethylene Terephthalate Glycol (PET-G) and MED 857 (DraftWhite), in the designing and developing of customized robotic grippers. The primary focus of made analyses was oriented on materials characterization, both experimentally and analytically. Computer-Aided Engineering (CAE) methods were employed to simulate bending experiments, allowing for a comprehensive analysis of the mechanical behavior of the selected materials. These simulations were validated through physical bending experiments using samples fabricated via 3D printing technologies, including Fused Filament Fabrication (FFF) for PET-G and PEKK, as well as Jetted Photopolymer (PolyJet) technology employing UV Resin for MED 857. The findings of this research provided advantages of utilizing advanced materials like PEKK in low-cost robotic grippers for biomechatronic applications. The experimental and analytical approaches offer valuable insights into material selection, design optimization, and the development of cost-effective high-performing robotic systems with a wide range of applications in the field of biomechatronics.